Prevalence and Associated Factors to Uvula Cutting on Under Five Children in Amhara Region, Debre Birhan Town, 2016/ 2017 - Kebede, Kabtamu; Mulate, Kassie; Chekole, Msanew; Zewdie, Amakelew; Redahegn, Hirut; Demelash, Alebachew; Wasinad, Sisay (International Journal of Pediatrics and Child Health, 2017)
Background: Traditional uvula cutting, a procedure which consists of cutting part or the entire uvula, it is a common practice in sub-Saharan Africa. In Ethiopia, studies conducted so far were very limited and focused on adult TMP. uvula cutting is commonly practiced in the northern part of Ethiopia but rarely seen in Gambela region. Objective: The aim of the study was to assess the prevalence and associated factors on uvula cutting in DBT, in 2015. Methods: A community based cross-sectional study design was conducted from January seven to February eight2015. The data was collected by trained diploma nurses and was analyzed by using EPI-Info 3.5.4,spss version 16 computer software, the result was presented in the form of text, tables, graphs and pi-chart. Result: The prevalence of uvula cutting among under five children was 23.7%. In this study occupational status, house wife, farmer and others like bar tender) and current age of child are significantly associated with the practice of uvula cutting.